Bioassay-directed isolation of active compounds with antiyeast activity from a cassia fistula seed extract - Jothy, S.L.; Zakaria, Z.; Chen, Y.; Lau, Y.L.; Latha, L.Y.; Shin, L.N.; Sasidharan, S. (2011)
Background and objective: Cassia fistula L belongs to the family Leguminosae, and it is one of the most popular herbal products in tropical countries. C. fistula seeds have been used as a herbal medicine and have pharmacological activity which includes anti-bacterial, anti-fungal, and antioxidant properties. The goal of this study was to identify compounds from C. fistula seeds which are responsible for anti-Candida albicans activity using bioassay-directed isolation. Results: The preliminary phytochemical screening of the plant seed revealed the presence of anthraquinones, flavonoids, saponins, tannins and terpenoids. The isolation of active compounds was carried out in four steps: multiple extractions, fractionation using column chromatography and purification using preparative thin-layer chromatography (TLC) and liquid chromatography/mass spectrometry (LC/MS). The structure of separated compounds was determined on the basis of mass spectrometry data. One compound was identified is roseanone. Conclusions: The MS analysis on the active fraction from seed extract of C. fistula confirmed the presence of roseanone with antiyeast activity.